Lesbian Police Officers: A Review of Television Portrayals and Their Lived Experiences. (4th May 2021) - Colvin, Roddrick; Moton, Lauren
Abstract : This exploratory research considers television's portrayals of lesbian police officers from the first known character in 1986 through the present. We examine the degree to which depictions of lesbian police officers on television advance or hinder social equity in law enforcement.